APPLYING HOWARD GARDNER’S THEORY OF MULTIPLE INTELLIGENCES TO JENNY MELLOR’S CHARACTER IN THE MOVIE “AN EDUCATION” - Muhammad Ilham Ali; Rutmintauli Simanjuntak; Herminus Efrando Pabur (Elite : English and Literature Journal, 2023)
"An Education" is a drama movie from 2009 that was directed by Lone Scherfig and produced by Finola Dwyer and Amanda Posey. It features an ensemble cast including Carey Mulligan, Peter Sarsgaard, Alfred Molina, Rosamund Pike, Dominic Cooper, Emma Thompson, and Olivia Williams. The central character in the movie is Jenny Mellor, a hardworking 16-year-old student. Her parents have high hopes for her to attend Oxford University. However, Jenny's orderly life starts to change when she develops an unlikely relationship with David Goldman, a middle-aged man. This study examines the portrayal of Jenny Mellor, the main character in the movie "An Education," through the lens of Howard Gardner's theory of multiple intelligences. The study aims to analyze the various forms of intelligence that Jenny Mellor possesses and how they shape her personal and academic growth. Utilizing Gardner's theory, which acknowledges different types of intelligence beyond traditional academic measures, this study explores how Jenny's intellectual, social, emotional, and creative capacities are depicted in the movie. The analysis utilizes qualitative methods, including content analysis and narrative interpretation, to explore the diverse aspects of Jenny's intelligence. The findings reveal that Jenny demonstrates strengths in linguistic, logical-mathematical, interpersonal, and intrapersonal intelligence, while also displaying aptitude in other domains such as musical and Visual-Spatial intelligence. Furthermore, the study sheds light on how Jenny's diverse intelligences influence her decision-making, relationships, and overall development. This study contributes to a deeper appreciation of the multifaceted nature of intelligence and illuminates the character development of Jenny Mellor through the lens of Howard Gardner's theory.